Trinexapac-ethyl causes stimulatory effect on eucalyptus initial growth under nutritional deficiency - Bacha, Allan Lopes [UNESP]; Martins, Pedro de Figueiredo Rocha Barbosa [UNESP]; Alves, Pedro Luis da Costa Aguiar [UNESP]; de Paula, Rinaldo Cesar [UNESP] (Canadian Science Publishing, 2018)
Eucalyptus plants are sensitive to abiotic stresses in their initial growth, and nutritional deficiency is one of the most recurrent among them. Trinexapac-ethyl, which is a plant growth regulator, can positively affect eucalyptus, a response known as hormesis, possibly providing plants with greater tolerance to stress. The objective of this study was to evaluate the effect of trinexapac-ethyl at two application times, before planting (BP) or after planting (AP), in Eucalyptus urophylla under conditions of nutritional deficiency (NPK). Two experiments (one for each application time) were conducted simultaneously during 81 days after planting of eucalyptus in 15 L pots. The treatments consisted of three doses of trinexapac-ethyl (0, 30, and 60 g a.i.·ha−1) and four variations of nutrient supply: complete solution (NPK) and solutions without nitrogen (−N), without phosphorus (−P), and without potassium (−K). The variables of gas exchange, growth, and dry matter were evaluated. For both application times, trinexapac-ethyl had a positive effect on the root–shoot ratio of plants grown in −N and also positively affected some eucalyptus photosynthetic characteristics. In the AP application, the compound provided gains in height and dry matter, regardless of the nutrient supply. Under phosphorus deficiency, trinexapac-ethyl provided gains in total dry matter (BP) and leaf area (AP).
Keywords: Eucalyptus urophylla; Hormesis; Nitrogen; Phosphorus; Plant growth regulator